Morphological Characteristics of Araceae Plants in Liwa Botanical Garden, West Lampung - Risa Suryani Wilyasari; Yulianty Yulianty; Zulkifli Zulkifli; Endang Nurcahyani (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2020)
Araceae is one type of plant that has a fairly high level of diversity and also rich in benefits such as a source of food, ornamental plants, and medicine. Research on the characteristics of Araceae in Indonesia is still limited. The purpose of this study was to identify Araceaeplants based on morphological structure and analyze the morphological characteristics ofAraceae in Liwa Botanical Garden, West Lampung. This research was conducted from November 2019 to January 2020. Data were collected at Liwa Botanical Garden, WestLampung based on exploration and observation collection methods. Morphological structure data were analyzed as descriptive and qualitative. The parts of plants that are compared between Araceae plants are the shape, size of leaves, petiole, and inflorescences. Observations show that 21 genera of Araceae are consisting of 26 plants. Araceae plants have three different ways of life, namely terrestrial, epiphytic, and aquatic. The shape of the leaves is ovatus, cordatus, lanceolatus, cuneatus, needle, peltatus, sagittatus, hastatus, palmatisect, bipinnatisect and tripinnatisect. The characteristics of this plant have compound interest with cob types (spadix) which are covered by a spatha with two types of inflorescences, namely unisexual and bisexual.